Skiing economy and efficiency in recreational and elite cross-country skiers - Ainegren, M.; Carlsson, P.; Tinnsten, M.; Laaksonen, M. S. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate and compare skiing economy and gross efficiency in cross-country skiers of different performance levels, ages and genders; male recreational skiers and elite senior and junior cross-country skiers of both genders. The skiers performed tests involving roller skiing on a treadmill using the gear 3 and diagonal stride techniques. The elite cross-country skiers were found to have better skiing economy and higher gross efficiency (5-18%) compared with the recreational skiers (p < 0.05) and the senior elite had better economy and higher efficiency (4-5%) than their junior counterparts (p < 0.05), whereas no differences could be found between the genders. Also, large ranges in economy and gross efficiency were found in all groups. It was concluded that, in addition to VO2peak, skiing economy and gross efficiency have a great influence on the differences in performance times between recreational and junior and senior elite cross-country skiers, as well as between individual skiers within the different categories. Thus, we recommend cross-country skiers at all performance levels to test not only VO2peak, but also skiing economy and efficiency.